2013
DOI: 10.1371/journal.pone.0061230
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 89Zr-Labeled Human Anti-CD147 Monoclonal Antibody as a Positron Emission Tomography Probe in a Mouse Model of Pancreatic Cancer

Abstract: IntroductionPancreatic cancer is an aggressive cancer and its prognosis remains poor. Therefore, additional effective therapy is required to augment and/or complement current therapy. CD147, high expression in pancreatic cancer, is involved in the metastatic process and is considered a good candidate for targeted therapy. CD147-specfic imaging could be useful for selection of appropriate patients. Therefore, we evaluated the potential of a fully human anti-CD147 monoclonal antibody 059-053 as a new positron em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 26 publications
0
61
1
Order By: Relevance
“…The absorbed doses of the other organs are also considered tolerable because these absorbed doses are lower than the tolerance doses of those organs based on the findings of external‐beam radiation studies . This is supported by several previous studies using 90 Y‐labeled antibodies, which showed no severe toxicities induced by similar absorbed doses . Therefore, the risk of radiation‐induced toxicity from RIT with 90 Y‐labeled NZ‐12 is expected to be low, although further dosimetry studies in malignant mesothelioma patients are required.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The absorbed doses of the other organs are also considered tolerable because these absorbed doses are lower than the tolerance doses of those organs based on the findings of external‐beam radiation studies . This is supported by several previous studies using 90 Y‐labeled antibodies, which showed no severe toxicities induced by similar absorbed doses . Therefore, the risk of radiation‐induced toxicity from RIT with 90 Y‐labeled NZ‐12 is expected to be low, although further dosimetry studies in malignant mesothelioma patients are required.…”
Section: Discussionmentioning
confidence: 82%
“…45,46 This is supported by several previous studies using 90 Y-labeled antibodies, which showed no severe toxicities induced by similar absorbed doses. 10,47 Therefore, the risk of radiation-induced toxicity from RIT with 90 Y-labeled NZ-12 is expected to be low, although further dosimetry studies in malignant mesothelioma patients are required. that the antitumor effect by RIT is limited, especially in radioresistant tumors, compared with external-beam radiation therapy as a result of lower radiation dose rates of RIT.…”
Section: Radiation Therapy For Malignant Mesothelioma Patients Is Gener-mentioning
confidence: 99%
“…However, the remarkable accumulation of 89 Zr-aGPC3 in HCC tumorsgreater than 800 %ID/g-overshadows liver uptake, yielding tumor-to-liver ratios greater than 30 in the larger (3.8-mm-diameter) tumor model. This ratio is substantially higher than that achieved with most other antibody probes, which have tumor-to-liver ratios ranging from 1.5 to 4 (10,16,(18)(19)(20) at their optimal time points after injection of 89 Zrlabeled antibody. These values are consistent with 89 Zr-aGPC3 uptake in smaller (,1-mmdiameter) tumors of the liver with a tumor-toliver ratio of 1.49-1.57 at 3-6 d after injection.…”
mentioning
confidence: 66%
“…Mab#58, and the control antibody were conjugated with p -isothiocyanatobenzyl-desferrioxamine B (DF; Macrocyclics, Dallas, TX, USA) at DF at an antibody molar ratio of 3:1, as previously described [ 29 ]. The conjugation ratio of DF to antibody was estimated to be 2.3:1 to 2.5:1, as determined by size exclusion chromatography using a PD10 column (GE Healthcare, Buckinghamshire, UK) before purification.…”
Section: Methodsmentioning
confidence: 99%